A proteção parental no direito do trabalho à luz da ética e da proteção da dignidade integral da pessoa humana - Marques, Deisi Machini [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Throughout history there have always been changes in behavior and, consequently, of society, and in this way, the laws should always move to adapt to the new realities. The last decades have been marked by radical changes and accelerated. The consolidation of democracies, the technological development, the massive entry of women in the labour market, changes in the concept of family, as well as on its structure, lead to society, businesses and the State to rethink the ethical criteria and human values in labor relations. In academia, new periodicals began to emerge about the issue of parental protection and the need for its deployment in the country legislation, so that its effects may impact the well-being or quality of life of individuals and the collective. The complex and extensive changes in social, political and economic structures, especially those experienced from the second half of the 20th century, had an impact on national legal order. Facing the increasing demands arising from social changes, and with the enactment of the 1988 Federal Constitution, is required the modernization of national legislation, deploying new or expanding some existing institutes became inconceivable certain interpretations infra legislation, so that several institutes of various branches of the law found themselves obsolete and incompatible with the social reality. In this way, the concept of family until then proclaimed that he as family structure to match the organization according to the hierarchical and patriarchal order enshrined by marriage; needed to be reviewed. The election of the principle of human dignity as one of the guidelines of the democratic State of law, gave a new conceptual redesign of it's family. The legal branch of the labor law also suffered constitutional influence, so that labour law institutes need to be interpreted in the light of the Constitution. In this context of significant modifications of legal hermeneutics, on...

Ao longo da história sempre houve mudanças no comportamento do homem e, consequentemente, da sociedade, e desta forma, as legislações sempre devem avançar no sentido de se adequar às novas realidades. As últimas décadas, têm sido marcadas por mudanças radicais e de forma aceleradas. A consolidação das democracias, o desenvolvimento tecnológico, a entrada maciça das mulheres do mercado de trabalho, as mudanças no conceito de família, bem como na sua estrutura, levam a sociedade, as empresas e o Estado a repensar os critérios éticos e os valores humanos nas relações de trabalho. No meio acadêmico, começaram a surgir novas publicações periódicas sobre a questão da proteção parental e a necessidade de sua implantação na legislação pátria, para que os seus efeitos possam impactar no bem-estar ou na qualidade de vida dos indivíduos e da coletividade. As complexas e extensas mudanças das estruturas sociais, políticas e econômicas, principalmente as vivenciadas a partir da segunda metade do século XX, repercutiram na ordem jurídica nacional. Frente às crescentes demandas advindas das mudanças sociais, e com a promulgação da Constituição Federal de 1988, é necessário a modernização da legislação nacional, implantando novos institutos ou ampliando alguns existentes, tornaram-se inconcebíveis certas interpretações à legislação infraconstitucional, de modo que vários institutos de diversos ramos do direito viram-se obsoletos e incompatíveis com a realidade social. Dessa maneira, o conceito de família até então apregoado, que consagrava como estrutura familiar àquela que correspondia à organização segundo a ordem patriarcal hierarquizada e sacramentada pelo casamento; precisou ser revisto. A eleição do princípio da dignidade humana como uma das diretrizes do Estado Democrático de Direito, conferiu uma nova reformulação conceitual do que é família. O ramo jurídico do direito do trabalho...
Keywords: Direito; Direitos humanos; Família - Aspectos sociais; Dignidade; Igualdade - Aspectos jurídicos